Radel-based membranes with pyridine and imidazole side groups for high temperature polymer electrolyte fuel cells - Hink, Steffen; Ngoc My Hanh Duong; Henkensmeier, Dirk; Kim, Jin Young; Jang, Jong Hyun; Kim, Hyoung-Juhn; Han, Jonghee; Nam, Suk-Woo (Elsevier BV, 2015)
Polysulfone-based membranes with pyridine (PY) side chains, crosslinked by imidazole (IM) groups, are synthesised, doped with phosphoric acid (PA) and characterised in the hydrogen/air fuel cell at 160 degrees C. It is shown that the bisphenol A (BPA) group of Udel P-3500 (Solvay) acts as a breaking point, and Radel R-5000 NT (Solvay)-based membranes, in which BPA is substituted for biphenyl, show superior stability. Undoped membranes show thermal stability of up to 330 degrees C (3% weight loss, 10 degrees C/min, nitrogen). PA-doped membranes: The weight gain during acid doping is limited by the high crosslink density, and independent of the doping temperature. By varying the ratio of pyridine to imidazole units from 2:1 to 9:1, the PA uptake can be controlled between 200 and 500 wt%, respectively. The Young modulus increases with the crosslinking density from 12 to 129 MPa. Proton conductivity of the PY/IM 2:1 membrane at 160 degrees C reaches 59 mS/cm. In the fuel cell, the PY/IM 2:1 membrane achieved a potential of ca. 500 mV at 0.2 A/cm(2). After 430 h (330 h at 02 A/cm(2), then 0.4 A/cm(2)), the cell failed, and postmortem analysis suggested severe chemical degradation. Washing the membrane with ammonia solution before doping increased the stability further. (C) 2015 Elsevier B.V. All rights reserved.